Amorphous carbon-coated transition metal chalcogenide nanosheets and preparation method thereof

By peeling off the two-dimensional layered transition metal chalcogenide in a resin medium using a three-roll differential grinder, and forming an amorphous carbon cladding layer by freeze-drying and heat treatment, the problems of thickness controllability and performance stability are solved. It realizes efficient preparation of nanosheets suitable for multi-field applications.

CN115911301BActive Publication Date: 2025-02-25NANCHANG HANGKONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211269612.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2025-02-25
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently obtain carbon-coated transition metal chalcogenide nanosheets with controllable thickness, which limits its application in the fields of battery energy storage, electronic devices and catalysis.

Method used

The two-dimensional layered transition metal chalcogenide is peeled off in the resin medium by controlling the number of peeling and alcohol cleaning, and then lyophilized and heat-treated to form amorphous carbon Coated nanosheets.

Benefits of technology

The amorphous carbon-coated transition metal chalcogenide nanosheets prepared have excellent photoelectric properties, more stable structure and higher conductivity, and are suitable for battery energy storage, electronic devices and catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911301B_ABST
    Figure CN115911301B_ABST
Patent Text Reader

Abstract

The present invention provides an amorphous carbon-coated transition metal sulfide nanosheet and a preparation method thereof, the method mainly comprising the following steps: adding a two-dimensional layered transition metal sulfide to a resin and mixing by stirring in a water bath; peeling by a three-roll differential grinder, collecting from a discharge roller after repeated peeling cycles; removing part of the resin by alcohol dissolution, adding alcohol, and centrifuging and removing impurities by stirring and ultrasonic assistance in a centrifuge tube; placing the substance obtained after alcohol washing in a freeze dryer to obtain a flaky structure; and heat treating under an argon atmosphere to obtain an amorphous carbon-coated transition metal sulfide nanosheet. Compared with the prior art, the material prepared by the present invention has the characteristics of adjustable structure, good conductivity, excellent performance, good stability, etc., which can meet the application requirements of new materials in the fields of battery energy storage, electronic devices and catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an amorphous carbon-coated transition metal sulfide compound nanosheet and a preparation method thereof, and belongs to the technical field of battery energy storage, catalysis and electronic devices. Background Art

[0002] In 2004, two scientists from the University of Manchester in the UK, Andre Geim and Konstantin Novoselov, successfully exfoliated graphene sheets for the first time, which set off a research boom in the field of two-dimensional materials. Graphene has excellent optical, electrical, thermal and mechanical properties and is used in battery energy storage, electronic devices, catalysis and other fields, but its zero band gap defect makes it difficult to control the channel field effect, hindering its further application and development. This has prompted people to explore two-dimensional layered transition metal dichalcogenides (TMDCs) with graphene-like structures.

[0003] Two-dimensional layered transition metal chalcogenides have a layered structure similar to graphene that is bound by van der Waals forces, and have special band structures, semiconductor or superconducting properties, and good mechanical properties. They have broad application prospects in many fields such as electronic energy storage and nanoelectronic devices, and have attracted the interest of many researchers. They have become a hot topic in the field of low-dimensional functional materials in recent years. As negative electrode materials for ion batteries, metal chalcogenides and metal selenides have high theoretical specific capacities. Compared with commercialized graphite negative electrode materials, transition metal chalcogenides have abundant redox reaction sites, making their specific capacity several times that of graphite materials. However, their large volume expansion, severe pulverization, and poor conductivity also have a great impact on the electrochemical performance of lithium-ion batteries.

[0004] When two-dimensional layered transition metal chalcogenides are coated with a certain thickness of carbon and thinned by block exfoliation, the performance of the material is significantly improved in various fields.

[0005] Traditionally, the acquisition of two-dimensional layered transition metal chalcogenide micro-nano flakes can be divided into two categories: "top-down" exfoliation method and "bottom-up" synthesis method. "Top-down" means that the material is operated from large to small, and the material is exfoliated into a state with a smaller number of layers by physical methods. Common methods include: ball milling mechanical exfoliation method, electrochemical intercalation method, liquid phase exfoliation method, etc.; "bottom-up" means that the material is operated from small to large, and a layered nano-scale film is obtained by chemical synthesis method. There are several common preparation methods: chemical vapor deposition (CVD), hydrothermal and solvothermal methods, etc. Most of these traditional methods do not meet the development needs of today's society. Like the traditional ball milling mechanical exfoliation method in "top-down", the obtained material has the advantages of uniform crystal structure, high purity, and few surface defects. However, its disadvantages such as low production efficiency and poor controllability of the number of layers limit its large-scale production; the electrochemical intercalation method has a short reaction time and low environmental requirements, but the uncontrollability of embedded ions may affect the properties of the material, thus limiting the further application of this method. The "bottom-up" chemical vapor deposition (CVD) method has the advantages of high purity, controllable number of layers, no need for too high a vacuum degree, and low cost, but the preparation technology is still immature and needs further research; the hydrothermal and solvothermal methods are simple to operate and have high sample purity, but the disadvantages of long reaction time, invisible reaction process, and uncontrollable product thickness limit the further development of this technology.

[0006] Therefore, how to efficiently obtain carbon-coated transition metal chalcogenide nanosheets with controllable thickness through effective technical approaches is the key to the material's excellent performance and long-term stability.

[0007] In view of this, it is indeed necessary to propose an amorphous carbon-coated transition metal sulfide compound nanosheet and a preparation method thereof to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to provide an amorphous carbon-coated transition metal sulfide compound nanosheet and a preparation method thereof, which can meet the requirements of electronic devices, battery energy storage, catalysis and other fields for excellent performance and high stability of transition metal sulfide compounds with controllable carbon content.

[0009] To achieve the above object, the present invention provides a method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets, which mainly comprises the following steps:

[0010] Step 1, adding 1-20 wt% of a two-dimensional layered transition metal sulfide compound to 80-99 wt% of a resin, and mixing by stirring in a water bath at 40-70° C. for 10-30 min to obtain a mixture A;

[0011] Step 2, the mixture A obtained in step 1 is peeled off by a three-roll differential speed grinder, and after repeated peeling, a mixture B of two-dimensional layered transition metal sulfide nanosheets and resin is collected from a discharge roller;

[0012] Step 3, removing part of the resin by dissolving with alcohol, adding alcohol to the mixture B of the two-dimensional layered transition metal chalcogenide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating step 3 and continuing to wash with alcohol, and finally centrifuging to obtain substance C;

[0013] Step 4, placing the substance C obtained after washing with alcohol in a freeze dryer, and freeze drying it in a vacuum environment at -50°C to -30°C to obtain a substance D with a flaky structure;

[0014] Step 5: Place the freeze-dried substance D in a tube furnace for heat treatment under an argon atmosphere at a temperature of 1-5°C min -1 The heating rate is increased to 500-700°C, kept at this temperature for 1-5 hours, and then naturally cooled to room temperature to obtain amorphous carbon-coated transition metal sulfide nanosheets.

[0015] As a further improvement of the present invention, the chemical formula of the two-dimensional layered transition metal chalcogenide is MX2, wherein M is one of V, Ti, Zr, Ta, Nb, Mo or W, and X is one of S, Se or Te.

[0016] As a further improvement of the present invention, the length and width of the two-dimensional layered transition metal sulfide compound are between 5 μm and 1 mm, and the thickness is between 1 and 100 μm.

[0017] As a further improvement of the present invention, the resin is one of phenolic resin, epoxy resin or polyethylene resin.

[0018] As a further improvement of the present invention, the thickness of amorphous carbon on the two-dimensional layered transition metal sulfide compound nanosheet is determined by the number of cyclic peeling of the three-roll differential speed grinder, the alcohol content and the number of alcohol cleanings, wherein the number of cyclic peeling is 8-15 times, the alcohol content is 50-200 vol%, and the number of alcohol cleanings is 2-8 times.

[0019] As a further improvement of the present invention, the three-roll differential grinder includes a discharge roller N1, a center roller N2 and a feed roller N3, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 is 1:3:9, and during the cyclic peeling process, the gap between the center roller N2 and the feed roller N3 is always larger than the gap between the discharge roller N1 and the center roller N2.

[0020] As a further improvement of the present invention, during the 1st to 4th cyclic peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 20 and 100 μm.

[0021] As a further improvement of the present invention, during the 5th to 8th cycle peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 5 and 20 μm.

[0022] As a further improvement of the present invention, after the ninth cyclic peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 0.5 and 5 μm.

[0023] To achieve the above objectives, the present invention also provides an amorphous carbon-coated transition metal chalcogenide nanosheet, which is prepared using the preparation method of the amorphous carbon-coated transition metal chalcogenide nanosheet as described above, wherein the amorphous carbon-coated transition metal chalcogenide nanosheet comprises 95-99.9wt% of two-dimensional layered transition metal chalcogenide nanosheets and 0.1-5wt% of amorphous carbon.

[0024] The beneficial effects of the present invention are as follows: the amorphous carbon-coated layered transition metal sulfide compound nanosheets finally prepared by the present invention have a unique layered structure, a large specific surface area and a high surface activity, and have a more stable structure, higher conductivity, a bandgap width that is dependent on the number of layers, excellent photoelectric properties such as energy equivalent to visible light, a larger switching ratio, etc. These changes make the material have good application prospects in the fields of battery energy storage, electronic devices, catalysis, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 In the figure, (a) is a schematic diagram of the present invention in which WS2 is peeled off in a resin by a three-roll differential speed grinder to obtain a sheet material, and (b) is a schematic diagram of the relationship between the number of layers of the product after peeling and the number of peeling times (taking 1024 layers as an example) and a schematic diagram of the structure of different thicknesses of the micron-thick raw material MX2 peeled off.

[0026] Figure 2 This is the SEM image of micron-sized molybdenum sulfide before peeling.

[0027] Figure 3 This is a SEM image of the molybdenum sulfide nanosheet product formed after the molybdenum sulfide is peeled off by three-roll grinding in phenolic resin in Example 1, washed with alcohol, freeze-dried and heat-treated.

[0028] Figure 4This is a TEM image of the amorphous carbon-coated molybdenum sulfide nanosheets prepared in Example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] It should be noted here that in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.

[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0032] The present invention aims to use a three-roller differential grinding and stripping technology to form a shear force in a resin medium through the different speed differences of three rollers to strip a two-dimensional layered transition metal sulfide compound with a thickness of micrometers and connected by weak van der Waals forces between layers, and the carbon content of the layered transition metal sulfide compound after stripping is controllable, and the structure and performance of the layered transition metal sulfide compound are similar to or even better than graphene, and can make up for the defect of zero band gap of graphene, so as to prepare corresponding nanosheets and resin mixtures. The resin in the washing mixture is mainly dissolved by alcohol, and after freeze drying and heat treatment, a pyrolyzed amorphous carbon-coated transition metal sulfide nanosheet is obtained, and the thickness of the transition metal sulfide nanosheet is regulated by controlling the number of three-roller stripping times, and the thickness of the pyrolyzed amorphous carbon coating the transition metal sulfide nanosheet is controlled by controlling the alcohol content and the number of washing times. The remaining resin is regulated to control the thickness of the pyrolyzed amorphous carbon coating the transition metal sulfide nanosheet, thereby meeting the excellent performance and high stability requirements of transition metal sulfide compounds with controllable carbon content in the fields of electronic devices, battery energy storage, catalysis, etc.

[0033] like Figure 1 and Figure 2 As shown, the present invention discloses a method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets, by which amorphous carbon-coated two-dimensional layered transition metal chalcogenide nanosheets with controllable thickness can be prepared, which can be applied to electronic devices. The method for preparing the amorphous carbon-coated transition metal chalcogenide nanosheets mainly includes the following steps:

[0034] Step 1, adding 1-20 wt% of a two-dimensional layered transition metal sulfide compound to 80-99 wt% of a resin, and mixing by stirring in a water bath at 40-70° C. for 10-30 min to obtain a mixture A;

[0035] Step 2, the mixture A obtained in step 1 is peeled off by a three-roll differential speed grinder, and after repeated peeling, a mixture B of two-dimensional layered transition metal sulfide nanosheets and resin is collected from a discharge roller;

[0036] Step 3, removing part of the resin by dissolving with alcohol, adding alcohol to the mixture B of the two-dimensional layered transition metal chalcogenide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating step 3 and continuing to wash with alcohol, and finally centrifuging to obtain substance C;

[0037] Step 4, placing the substance C obtained after washing with alcohol in a freeze dryer, and freeze drying it in a vacuum environment at -50°C to -30°C to obtain a substance D with a flaky structure;

[0038] Step 5: Place the freeze-dried substance D in a tube furnace for heat treatment under an argon atmosphere at a temperature of 1-5°C min -1 The heating rate is increased to 500-700°C, kept at this temperature for 1-5 hours, and then naturally cooled to room temperature to obtain amorphous carbon-coated transition metal sulfide nanosheets.

[0039] Steps 1 to 5 are described in detail below.

[0040] In step 1, the chemical formula of the two-dimensional layered transition metal chalcogenide is MX2, wherein M is one of V, Ti, Zr, Ta, Nb, Mo or W, and X is one of S, Se or Te. The length and width of the two-dimensional layered transition metal chalcogenide are between 5 μm and 1 mm, and the thickness is between 1 and 100 μm. The resin is one of phenolic resin, epoxy resin or polyethylene resin.

[0041] In step 2, the thickness of amorphous carbon on the two-dimensional layered transition metal sulfide compound nanosheets is determined by the number of cyclic peeling of the three-roll differential speed grinder, the alcohol content and the number of alcohol washings, wherein the number of cyclic peeling is 8-15 times, the alcohol content is 50-200 vol%, the number of alcohol washings is 2-8 times, and the finally obtained two-dimensional layered transition metal sulfide compound nanosheets account for 95-99.9wt% of the total mass, and the amorphous carbon accounts for 0.1-5wt% of the total mass.

[0042] The three-roll differential grinder includes a discharge roller N1, a center roller N2 and a feed roller N3, wherein the speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 is 1:3:9, and during the cyclic peeling process, the gap between the center roller N2 and the feed roller N3 is always larger than the gap between the discharge roller N1 and the center roller N2.

[0043] It should be noted that the roller spacing is different in different numbers of cyclic peeling. For example, during the 1st to 4th cyclic peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 20 and 100 μm; during the 5th to 8th cyclic peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 5 and 20 μm; after the 9th cyclic peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 0.5 and 5 μm.

[0044] The following is a detailed description with reference to the embodiments and comparative examples.

[0045] like Figure 3 and Figure 4 As shown, embodiment 1 specifically includes the following steps:

[0046] Step 1, adding 15wt% of a two-dimensional layered molybdenum sulfide (MoS2) raw material having a length and width of 100μm and a thickness of 15μm to 85wt% of a phenolic resin, and stirring and mixing the mixture in a 50°C water bath for 15min to obtain a mixture A;

[0047] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 15 cycles of peeling, a mixture B of molybdenum sulfide nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th to 15th cycles of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0048] Step 3, adding 100 vol% alcohol to the mixture B of the molybdenum sulfide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 4 times, and finally centrifuging to obtain substance C;

[0049] Step 4, placing the substance C obtained after washing with alcohol in a freeze dryer, and freeze drying it under vacuum and at -45°C to obtain a substance D that can maintain a flaky structure;

[0050] Step 5: Place the freeze-dried substance D in a tube furnace under an argon atmosphere for heat treatment at a temperature of 4°C min-1 from room temperature. -1 The temperature was raised to 600°C at a rate of 100 °C, kept at that temperature for 3 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated molybdenum sulfide nanosheets with a certain thickness.

[0051] Weigh 0.07 g of amorphous carbon-coated molybdenum sulfide nanosheets prepared in this example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil, vacuum dry at 120 ° C for 10 h, cut into discs with a diameter of 12 mm, and assemble in an argon atmosphere glove box, using metal lithium sheet as the counter electrode, 1 M LiPF6 solution (solvent EC: DEC volume ratio of 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The amorphous carbon-coated molybdenum sulfide nanosheet material was subjected to constant current charge and discharge tests. The first charge / discharge specific capacity as the negative electrode of the lithium-ion battery was 1112 / 1480mA h g -1 After 100 cycles, the discharge capacity is 964 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of amorphous carbon-coated molybdenum sulfide nanosheets shows that the capacity is still 762mAh g after 500 cycles. -1 , 1A g -1 The capacity retention rate after 500 cycles at the same current density was 99%.

[0052] Under the same preparation conditions and parameters, the sodium battery was assembled and the sodium electrical performance was tested. The sodium metal sheet was used as the counter electrode, 1M NaClO4 solution (solvent EC:PC volume ratio is 1:1) was used as the electrolyte, and the glass fiber whatmanGF / A was used as the separator to assemble a CR2032 type sodium button battery. At 25°C, at 100mA g -1 The voltage window was 0-3.0V at a current density of 1.5V and the constant current charge and discharge test was carried out on the amorphous carbon-coated molybdenum sulfide nanosheet material. The first charge / discharge specific capacity as the negative electrode of the sodium ion battery was 684.4 / 930mA hg -1After 100 cycles, the discharge capacity is 561.6 mAh g -1 .

[0053] Under the same preparation conditions and parameters, potassium battery assembly and potassium electrical performance test were carried out, with metal potassium sheet as the counter electrode, 1M KPF6 solution (solvent: DIGLYME) as the electrolyte, and glass fiber Whatman GF / A as the separator, to assemble a CR2032 button potassium battery. At 25°C, at 100mA g -1 The voltage window was 0-3.0V at a current density of 1.5V and the constant current charge and discharge test was carried out on the amorphous carbon-coated molybdenum sulfide nanosheet material. The first charge / discharge specific capacity of the negative electrode of the potassium ion battery was 492.5 / 650mA hg -1 After 100 cycles, the discharge capacity is 383 mAh g -1 .

[0054] Embodiment 2 specifically comprises the following steps:

[0055] Step 1, adding 14 wt% of a two-dimensional layered molybdenum sulfide raw material having a length and width of 100 μm and a thickness of 15 μm to 86 wt% of a phenolic resin, and stirring and mixing the mixture in a 50° C. water bath for 10 min to obtain a mixture A;

[0056] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 10 cycles of peeling, a mixture B of molybdenum sulfide nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th to 10th cycles of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0057] Step 3, adding 100 vol% alcohol to the mixture B of the molybdenum sulfide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing it in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 3 times, and finally centrifuging to obtain substance C;

[0058] Step 4: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -40°C to obtain a substance D that can maintain a flaky structure.

[0059] Step 5: Place the freeze-dried substance D in a tube furnace under an argon atmosphere for heat treatment at a temperature of 2°C min-1 from room temperature. -1 The temperature was raised to 600°C at a rate of 100 °C, kept at that temperature for 3 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated molybdenum sulfide nanosheets with a certain thickness.

[0060] Weigh 0.07 g of amorphous carbon-coated molybdenum sulfide nanosheets prepared in this example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil, vacuum dry at 120 ° C for 10 h, cut into discs with a diameter of 12 mm, and assemble in an argon atmosphere glove box, using metal lithium sheet as the counter electrode, 1 M LiPF6 solution (solvent EC: DEC volume ratio of 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of amorphous carbon-coated molybdenum sulfide nanosheets is carried out. The first charge / discharge specific capacity as the negative electrode of lithium-ion battery is 1022.5 / 1310mA hg -1 After 100 cycles, the discharge capacity is 830 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of amorphous carbon-coated molybdenum sulfide nanosheets is carried out. After 500 cycles, the capacity is still 620mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the current density was 92%.

[0061] Embodiment 3 specifically comprises the following steps:

[0062] Step 1, adding 10 wt% of a two-dimensional layered tungsten sulfide (WS2) raw material with a length and width of 150 μm and a thickness of 10 μm to 90 wt% of a phenolic resin, and stirring and mixing the mixture in a 60° C. water bath for 20 min to obtain a mixture A;

[0063] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder. After 9 cycles of peeling, a mixture B of WS2 nanosheets and resin is collected from the discharge roller, wherein the speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9. During the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th cycle of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0064] Step 3, add 150 vol% alcohol to the mixture B of WS2 nanosheets and resin obtained by stripping, stir and ultrasonically assist for 10 minutes, put it into a centrifuge tube for centrifugation and remove impurities, repeat this step to control the number of alcohol washing times to 5 times, and finally centrifuge to obtain substance C;

[0065] Step 4: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -50°C to obtain a substance D that can maintain a flaky structure.

[0066] Step 5: Place the freeze-dried substance D in a tube furnace under an argon atmosphere for heat treatment at a temperature of 4°C min-1 from room temperature. -1 The heating rate was increased to 700 °C, kept for 4 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated WS2 nanosheets with a certain thickness.

[0067] Weigh 0.07 g of the amorphous carbon-coated WS2 nanosheets prepared in this example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil. After vacuum drying at 120 ° C for 10 h, cut into discs with a diameter of 12 mm, and assemble in a glove box with an argon atmosphere. Use metal lithium sheet as the counter electrode, 1 M LiPF6 solution (solvent EC: DEC volume ratio is 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0V at the current density of 1.5V. The amorphous carbon-coated WS2 nanosheet material was subjected to constant current charge and discharge test. The first charge / discharge specific capacity as the negative electrode of the lithium-ion battery was 547 / 658 mA h g -1 After 100 cycles, the discharge capacity is 475 mAh g -1 ; At 25℃, at 1A g -1The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of amorphous carbon-coated two-dimensional layered WS2 nanosheet material was carried out. After 500 cycles, the capacity is still 384mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the same current density was 84%.

[0068] Embodiment 4 specifically comprises the following steps:

[0069] Step 1, adding 20wt% of a two-dimensional layered molybdenum selenide (MoSe2) raw material with a length and width of 500μm and a thickness of 60μm to 80wt% of phenolic resin, and stirring and mixing them in a 60°C water bath for 30min to obtain a mixture A;

[0070] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 14 cycles of peeling, a mixture B of MoSe2 nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 100 μm, and the gap between N2 and N1 is 50 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 25 μm, and the gap between N2 and N1 is 10 μm; during the 9th to 14th cycles of peeling, the gap between N3 and N2 is 5 μm, and the gap between N2 and N1 is 2 μm;

[0071] Step 3, add 100 vol% alcohol to the mixture B of the MoSe2 nanosheets and the resin obtained by peeling, stir and ultrasonically assist for 10 minutes, put it into a centrifuge tube for centrifugation and remove the impurities, repeat this step to control the number of alcohol washing times to 6 times, and finally centrifuge to obtain substance C;

[0072] Step 4: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -40°C to obtain a substance D that can maintain a flaky structure.

[0073] Step 5: Place the freeze-dried substance D in a tube furnace for heat treatment under an argon atmosphere, starting from room temperature at 3°C ​​min -1 The temperature was raised to 550°C at a rate of 100 °C, kept at that temperature for 4 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated MoSe2 nanosheets with a certain thickness.

[0074] Weigh 0.07 g of the amorphous carbon-coated MoSe2 nanosheets prepared in this example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil. After vacuum drying at 120°C for 10 h, cut into discs with a diameter of 12 mm, and assemble in a glove box with an argon atmosphere. Use metal lithium sheet as the counter electrode, 1 M LiPF6 solution (solvent EC:DEC volume ratio is 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25°C, at 100 mA g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The amorphous carbon-coated MoSe2 nanosheet material was subjected to constant current charge and discharge tests. The first charge / discharge specific capacities of the negative electrode of the lithium-ion battery were 953 / 1320 mA h g -1 After 100 cycles, the discharge capacity is 810 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of amorphous carbon-coated molybdenum sulfide nanosheets is carried out. After 500 cycles, the capacity is still 435mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the current density was 92%.

[0075] Comparative Example 1: Compared with Example 1, the preparation method is different in that there is no three-roll mill stripping and no phenolic resin heat treatment to form an amorphous carbon coating, but directly utilizes micron-sized two-dimensional layered molybdenum sulfide raw material.

[0076] Weigh 0.07 g of a two-dimensional layered molybdenum sulfide raw material with a length and width of 100 μm and a thickness of 15 μm, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder) of this comparative example, grind them thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat them on copper foil. After vacuum drying at 120°C for 10 hours, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use a metal lithium sheet as the counter electrode, a 1M LiPF6 solution (solvent EC:DEC volume ratio of 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25°C, at 100 mA g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of the two-dimensional layered molybdenum sulfide raw material is carried out. The first charge / discharge specific capacity as the negative electrode of the lithium-ion battery is 674 / 896mA hg -1After 100 cycles, the discharge capacity is 493 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of the micron-sized two-dimensional layered molybdenum sulfide raw material was carried out. After 500 cycles, the capacity is still 350mAh g -1 , 1Ag -1 The capacity retention rate after 500 cycles at the same current density was 76%.

[0077] Comparative Example 2,

[0078] Compared with Example 1, the preparation method is different in that there is no three-roll mill peeling but a phenolic resin heat treatment is used to form an amorphous carbon coating, which is an amorphous carbon-coated micron-sized two-dimensional layered molybdenum sulfide raw material. The specific preparation steps are as follows:

[0079] Step 1, adding 15 wt% of a two-dimensional layered molybdenum sulfide raw material having a length and width of 100 μm and a thickness of 15 μm to 85 wt% of a phenolic resin, and mixing the mixture in a 50° C. water bath by stirring for 15 min to obtain a mixture A;

[0080] Step 2, adding 100 vol% alcohol to the mixture B of the micron-sized two-dimensional layered molybdenum sulfide raw material and the resin obtained by stirring and mixing, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 4 times, and finally centrifuging to obtain substance C;

[0081] Step 3: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -45°C to obtain a substance D that can maintain a flaky structure.

[0082] Step 4: Place the freeze-dried substance D in a tube furnace under an argon atmosphere for heat treatment at a temperature of 4°C min-1 from room temperature. -1 The heating rate is increased to 600°C, kept for 3 hours, and then naturally cooled to room temperature to obtain an amorphous carbon-coated micron-sized two-dimensional layered molybdenum sulfide raw material with a certain thickness.

[0083] Weigh 0.07 g of the amorphous carbon-coated two-dimensional layered molybdenum sulfide raw material prepared in this comparative example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind them thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat them on copper foil. After vacuum drying at 120 ° C for 10 hours, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use metal lithium sheet as the counter electrode, 1M LiPF6 solution (solvent EC: DEC volume ratio is 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The amorphous carbon-coated two-dimensional layered molybdenum sulfide raw material prepared in the comparative example was subjected to constant current charge and discharge tests. The initial charge / discharge specific capacities of the negative electrode of the lithium-ion battery were 728 / 1035 mA h g -1 After 100 cycles, the discharge capacity is 658 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of the amorphous carbon-coated two-dimensional layered molybdenum sulfide raw material was carried out. After 500 cycles, the capacity is still 490mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the same current density was 82%.

[0084] Comparative Example 3,

[0085] Compared with Example 1, the difference between this preparation method and Example 1 is that there is a three-roll mill peeling but no phenolic resin heat treatment to form an amorphous carbon coating, and the two-dimensional layered molybdenum sulfide nanosheets are formed by peeling. The specific preparation steps are as follows:

[0086] Step 1, adding 15 wt% of a two-dimensional layered molybdenum sulfide raw material having a length and width of 100 μm and a thickness of 15 μm to 85 wt% of a phenolic resin, and mixing the mixture in a 50° C. water bath by stirring for 15 min to obtain a mixture A;

[0087] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 15 cycles of peeling, a mixture B of molybdenum sulfide nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th to 15th cycles of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0088] Step 3, adding 300 vol% of alcohol to the mixture B of the molybdenum sulfide nanosheets and the resin obtained by exfoliation, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 15 times, and finally centrifuging to obtain substance C until the resin is completely eliminated;

[0089] Step 4: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -45°C to obtain a substance D that can maintain a flaky structure.

[0090] Weigh 0.07 g of molybdenum sulfide nanosheets (without amorphous carbon coating) prepared by peeling in this comparative example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil. After vacuum drying at 120 ° C for 10 h, cut into discs with a diameter of 12 mm, and assemble in a glove box with argon atmosphere, using metal lithium sheet as the counter electrode, 1M LiPF6 solution (solvent EC: DEC volume ratio of 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0 V at a current density of 1.5 V. The molybdenum sulfide nanosheets (without amorphous carbon coating) prepared by exfoliation of the comparative example were subjected to constant current charge and discharge tests. The initial charge / discharge specific capacities of the negative electrode of the lithium-ion battery were 925 / 1164 mAh g -1 After 100 cycles, the discharge capacity is 739 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at a current density of 1.5V. The constant current charge and discharge test of the molybdenum sulfide nanosheet (without amorphous carbon coating) material was carried out. After 500 cycles, the capacity was still 527mAh g -1 , 1A g -1The capacity retention rate after 500 cycles at the same current density was 86%.

[0091] Comparative Example 4,

[0092] Compared with Example 1, the difference between the preparation method and Example 1 is that the drying method used is drying instead of freeze drying, and the amorphous carbon-coated exfoliated molybdenum sulfide nanosheets are formed by drying. The specific preparation steps are as follows:

[0093] Step 1, adding 15 wt% of a two-dimensional layered molybdenum sulfide raw material having a length and width of 100 μm and a thickness of 15 μm to 85 wt% of a phenolic resin, and mixing the mixture in a 50° C. water bath by stirring for 15 min to obtain a mixture A;

[0094] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 15 cycles of peeling, a mixture B of molybdenum sulfide nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th to 15th cycles of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0095] Step 3, adding 100 vol% alcohol to the mixture B of the molybdenum sulfide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 4 times, and finally centrifuging to obtain substance C;

[0096] Step 4: Place the substance C obtained after washing with alcohol in an oven and dry it at 50° C. to obtain substance D.

[0097] Step 5: Place the dried material D in a tube furnace for heat treatment under an argon atmosphere, starting from room temperature at 4°C min -1 The temperature was raised to 600°C at a rate of 100 °C, kept at that temperature for 3 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated molybdenum sulfide nanosheets with a certain thickness.

[0098] Weigh 0.07 g of amorphous carbon-coated molybdenum sulfide nanosheets prepared by drying with drying technology (not freeze-drying technology) and further heat treatment, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder) prepared by peeling in this comparative example, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil, vacuum dry at 120°C for 10 hours, cut into discs with a diameter of 12 mm, and assemble in a glove box with argon atmosphere, using metal lithium sheet as the counter electrode, 1M LiPF6 solution (solvent EC:DEC volume ratio is 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25°C, at 100 mA g -1 The voltage window is 0.01-3.0V at the current density. The amorphous carbon-coated molybdenum sulfide nanosheet material prepared by exfoliation of the comparative example is subjected to constant current charge and discharge test. The initial charge / discharge specific capacity as the negative electrode of the lithium-ion battery is 1008 / 1304 mA h g -1 After 100 cycles, the discharge capacity is 820 mAh g -1 ; At 25℃, at 1A g -1 The voltage window is 0.01-3.0V at the current density. The amorphous carbon-coated molybdenum sulfide nanosheet material prepared by exfoliation of the comparative example is subjected to constant current charge and discharge test. After 500 cycles, the capacity is still 642mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the same current density was 90%.

[0099] Comparative Example 5,

[0100] The difference between this preparation method and Example 1 is that the number of times the phenolic resin is washed is different. Example 1 washes 4 times, while this comparative example 5 washes 2 times. The purpose is to make the carbon coating thickness different during the subsequent heat treatment. The specific preparation steps are as follows:

[0101] Step 1, adding 15 wt% of a two-dimensional layered molybdenum sulfide raw material having a length and width of 100 μm and a thickness of 15 μm to 85 wt% of a phenolic resin, and mixing the mixture in a 50° C. water bath by stirring for 15 min to obtain a mixture A;

[0102] Step 2, the mixture A obtained in step 1 is peeled by a three-roll differential speed grinder, and after 15 cycles of peeling, a mixture B of molybdenum sulfide nanosheets and resin is collected from the discharge roller, wherein the rotation speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 of the three-roll differential speed grinder is 1:3:9, and during the 1st to 4th cycles of peeling, the gap between N3 and N2 is 50 μm, and the gap between N2 and N1 is 20 μm; during the 5th to 8th cycles of peeling, the gap between N3 and N2 is 10 μm, and the gap between N2 and N1 is 5 μm; during the 9th to 15th cycles of peeling, the gap between N3 and N2 is 3 μm, and the gap between N2 and N1 is 1 μm;

[0103] Step 3, adding 100 vol% alcohol to the mixture B of the molybdenum sulfide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating this step to control the number of alcohol washing times to 2 times, and finally centrifuging to obtain substance C;

[0104] Step 4: Place the substance C obtained after washing with alcohol in a freeze dryer and freeze-dry it in a vacuum environment at -45°C to obtain a substance D that can maintain a flaky structure.

[0105] Step 5: Place the freeze-dried substance D in a tube furnace under an argon atmosphere for heat treatment at a temperature of 4°C min-1 from room temperature. -1 The temperature was raised to 600°C at a rate of 100 °C, kept at that temperature for 3 h, and then naturally cooled to room temperature to obtain amorphous carbon-coated molybdenum sulfide nanosheets with a certain thickness.

[0106] Weigh 0.07 g of amorphous carbon-coated molybdenum sulfide nanosheets prepared by peeling in this comparative example, 0.015 g of acetylene black (conductive agent), and 0.015 g of PVDF (HSV900, binder), grind thoroughly, add 0.4 mL of NMP to disperse and mix, and then evenly coat on copper foil. After vacuum drying at 120 ° C for 10 h, cut into discs with a diameter of 12 mm, and assemble in a glove box with argon atmosphere. Use metal lithium sheet as the counter electrode, 1M LiPF6 solution (solvent EC: DEC volume ratio is 1:1) as the electrolyte, and Celegard2400 as the diaphragm to assemble into a CR2032 type button lithium battery. At 25 ° C, at 100 mA g -1 The voltage window is 0.01-3.0V at the current density. The amorphous carbon-coated molybdenum sulfide nanosheet material prepared by exfoliation in this comparative example is subjected to constant current charge and discharge test. The initial charge / discharge specific capacity as the negative electrode of the lithium-ion battery is 927 / 1210 mA h g -1 After 100 cycles, the discharge capacity is 767 mAh g -1 ; At 25℃, at 1A g-1 The voltage window is 0.01-3.0V at the current density. The amorphous carbon-coated molybdenum sulfide nanosheet material prepared by exfoliation of the comparative example is subjected to constant current charge and discharge test. After 500 cycles, the capacity is still 588mAh g -1 , 1A g -1 The capacity retention rate after 500 cycles at the same current density was 89%.

[0107] As shown in Table 1 below, the performance comparison between the embodiment and the comparative example is shown.

[0108] Table 1 Performance comparison between the examples and the comparative examples

[0109]

[0110] In summary, the amorphous carbon-coated transition metal sulfide compound nanosheet prepared by the present invention is a three-roll differential speed grinder that grinds and peels the raw material, overcomes the weak interlayer van der Waals force through the shear force generated by the three-roll differential speed and the interaction force between the high-viscosity resin and the two-dimensional layered transition metal sulfide compound, and controls the thickness of the transition metal sulfide compound nanosheet by controlling the number of three-roll peeling times, thereby achieving the purpose of peeling the two-dimensional layered transition metal sulfide compound large particles with a thickness of micrometer level into two-dimensional layered transition metal sulfide compounds with a thickness of nanometer level with controllable single layer, several layers, dozens of layers to dozens of layers, as shown in the attached Figure 1 Compared with the existing technology, this stripping method not only ensures the preparation of nano-sheet materials, but also has the advantages of uniform crystal structure, high purity, few surface defects, etc., and can adjust the relative number of layers of the product thickness, thereby adjusting the performance of the product, and also solves the problem of low production efficiency.

[0111] The phenolic resin, epoxy resin and polyethylene resin in the present invention are not only used as grinding media in the three-roll grinding process, but also as carbon sources for the subsequent coating and peeling of transition metal sulfide nanosheets. The technical difficulties that need to be overcome here are: (1) The content of the resin required in the process of peeling the two-dimensional layered transition metal sulfide compound MX2 needs to be more than 80wt% to effectively peel off MX2. If the resin content is low, it is difficult to effectively peel off MX2; (2) The carbon source of the subsequent coating and peeling of the transition metal sulfide nanosheet cannot be higher than 5wt%. If it is higher than this value, it will lead to a rapid decrease in charge and discharge capacity. Therefore, in the technology of the present invention, a resin containing more than 80wt% is used as a peeling medium to peel off a metal sulfide with a thickness of micrometers through a three-roll differential speed grinder to obtain a transition metal sulfide nanosheet and a resin mixture, and then most of the resin is washed off with alcohol and a small amount of resin is left to coat the sulfide nanosheet. After freeze-drying, the remaining small amount of resin is pyrolyzed to form amorphous carbon (the carbon content is controlled to be within 5wt%) to coat the transition metal sulfide nanosheet. Compared with traditional externally added nanocarbon, the amorphous carbon prepared in this way for coating metal chalcogenide nanosheets has better uniformity and dispersion.

[0112] The present invention prepares a transition metal sulfide compound nanosheet and a resin mixture in the early stage. After washing away part of the resin with alcohol, a small amount of part of the resin remains. Since the resin has a certain viscosity, compared with the traditional drying technology (part of the resin-coated sulfide compound nanosheet mixture is easy to form a paste agglomerate), the present invention adopts freeze-drying technology for processing, which can obtain a powder of the part of the resin-coated sulfide compound nanosheet with a very good dispersion effect, and maintain the layered effect after peeling.

[0113] The present invention regulates the residual resin content by controlling the alcohol content and the number of cleaning times, thereby controlling the thickness of amorphous carbon formed by pyrolysis and coating on transition metal chalcogenide nanosheets in an argon atmosphere, and controlling the carbon content to be ≤5wt%. The prepared amorphous carbon-coated transition metal chalcogenide nanosheet has the problems of volume expansion, severe pulverization and poor electrical conductivity existing in pure two-dimensional layered transition metal chalcogenides. The coated amorphous carbon of the present invention greatly increases the electrical conductivity of the material and better improves the structural stability of the metal chalcogenide, so that the metal chalcogenide has better performance and can be applied to more fields.

[0114] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets, characterized in that: The following steps are involved: Step 1, adding 1-20 wt% of a two-dimensional layered transition metal sulfide compound to 80-99 wt% of a resin, and mixing by stirring in a water bath at 40-70° C. for 10-30 min to obtain a mixture A; Step 2, the mixture A obtained in step 1 is peeled off by a three-roll differential speed grinder, and after repeated peeling, a mixture B of two-dimensional layered transition metal sulfide nanosheets and resin is collected from a discharge roller; Step 3, removing part of the resin by dissolving with alcohol, adding alcohol to the mixture B of the two-dimensional layered transition metal chalcogenide nanosheets and the resin obtained by peeling, stirring and ultrasonically assisting for 10 minutes, placing in a centrifuge tube for centrifugation and removing impurities, repeating step 3 and continuing to wash with alcohol, and finally centrifuging to obtain substance C; Step 4, placing the substance C obtained after washing with alcohol in a freeze dryer, and freeze drying it in a vacuum environment at -50°C to -30°C to obtain a substance D with a flaky structure; Step 5: Place the freeze-dried substance D in a tube furnace for heat treatment under an argon atmosphere at a temperature of 1-5°C min -1 The temperature is raised to 500-700°C at a rate of 1-5 hours, and then naturally cooled to room temperature to obtain amorphous carbon-coated transition metal chalcogenide nanosheets; The thickness of amorphous carbon on the two-dimensional layered transition metal sulfide compound nanosheet is determined by the number of cyclic peeling of the three-roll differential speed grinder, the alcohol content and the number of alcohol cleanings, wherein the number of cyclic peeling is 8-15 times, the alcohol content is 50-200 vol%, and the number of alcohol cleanings is 2-8 times.

2. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 1, characterized in that: The chemical formula of the two-dimensional layered transition metal chalcogenide is MX2, wherein M is one of V, Ti, Zr, Ta, Nb, Mo or W, and X is one of S, Se or Te.

3. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 1, characterized in that: The length and width of the two-dimensional layered transition metal sulfide compound are between 5 μm and 1 mm, and the thickness is between 1 and 100 μm.

4. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 1, characterized in that: The resin is one of phenolic resin, epoxy resin or polyethylene resin.

5. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 1, characterized in that: The three-roll differential grinder includes a discharge roller N1, a center roller N2 and a feed roller N3, wherein the speed ratio of the feed roller N3, the center roller N2 and the discharge roller N1 is 1:3:9, and during the cyclic peeling process, the gap between the center roller N2 and the feed roller N3 is always larger than the gap between the discharge roller N1 and the center roller N2.

6. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 5, characterized in that: During the 1st to 4th cycle peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 20 and 100 μm.

7. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 5, characterized in that: During the 5th to 8th peeling cycle, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 5 and 20 μm.

8. The method for preparing amorphous carbon-coated transition metal chalcogenide nanosheets according to claim 5, characterized in that: After the ninth cycle peeling, the gap between the center roller N2 and the feed roller N3 and the gap between the discharge roller N1 and the center roller N2 are both between 0.5 μm and 5 μm.

9. An amorphous carbon-coated transition metal chalcogenide nanosheet, characterized in that: The amorphous carbon-coated transition metal chalcogenide nanosheet is prepared by the preparation method of any one of claims 1 to 8, wherein the amorphous carbon-coated transition metal chalcogenide nanosheet comprises 95-99.9wt% of two-dimensional layered transition metal chalcogenide nanosheets and 0.1-5wt% of amorphous carbon.

Citation Information

Patent Citations

  • Composite active material for lithium secondary battery and method for producing same

    CN105164836A

  • Three-roller differential variable-curvature numerical control plate rolling machine

    CN114192622A